Biocontrol ability and action mechanism of dihydromaltophilin against Colletotrichum fructicola causing anthracnose of pear fruit. Issue 2 (19th October 2020) - Li, Chaohui; Tang, Bao; Cao, Shulin; Bao, Yan; Sun, Weibo; Zhao, Yancun; Liu, Fengquan
Abstract: BACKGROUND: Anthracnose caused by Colletotrichum fructicola is one of the most important diseases in pear fruit, resulting in huge economic losses. Public awareness of protecting the environment and food safety, together with pathogen resistance to many key fungicides have led to an urgent need to develop alternative strategies for controlling fruit diseases. Here, the antifungal activity of a natural product, dihydromaltophilin [heat‐stable antifungal factor (HSAF)], against C. fructicola in vitro and in vivo was investigated to determine its efficacy for anthracnose management. RESULTS: HSAF exhibited pronounced antifungal activity against in vitro mycelial growth of C. fructicola, with a half‐inhibition concentration of 0.43 mg L −1 . Hyphae treated with HSAF showed defects such as hyperbranching, swelling and depolarized growth. Conidia germination in the pathogen was inhibited by HSAF in a dose‐dependent manner. In the presence of 4 mg L −1 HSAF, conidia germination was significantly delayed, and germ tube growth was inhibited. HSAF at 8 mg L −1 completely blocked conidia germination in C. fructicola . In addition, HSAF disrupted coordination of cytokinesis with growth and nuclear division, induced reactive oxygen species production in conidia, and damaged the integrity of the conidia cell wall. Moreover, an in vivo test confirmed that 50 mg L −1 HSAF significantly reduced the development of anthracnose decay in pear fruit caused by C. fructicola . CONCLUSION: HSAF was highly effective in reducing pear anthracnose caused by C. fructicola and has great potential to become a new type of fruit preservative. Abstract : Dihydromaltophilin [heat‐stable antifungal factor (HSAF] showed pronounced antifungal activity against Colletotrichum fructicola in vitro and in vivo, and has great potential to become a new type of fruit preservative. © 2020 Society of Chemical Industry